1994
DOI: 10.1152/ajpheart.1994.266.1.h1
|View full text |Cite
|
Sign up to set email alerts
|

New experiments on shear modulus of elasticity of arteries

Abstract: Although the mechanical properties of blood vessels have been studied extensively, the shear modulus of the blood vessel wall is still unknown. New data on the shear modulus of elasticity of rat arteries and its variation with axial stretch and blood pressure are presented. The data were obtained from a new instrument designed and constructed by us to perform simultaneous torsion, inflation, and longitudinal stretching tests. It was found under physiological conditions (pressure = 120 mmHg or 16 kPa; longitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 0 publications
3
71
0
2
Order By: Relevance
“…Shear was studied by Deng et al (24), but was zero in the present study, hence a 3 and b 3 are irrelevant in the present experiment. When the strains E and E zz and stresses S , S zz were calculated from the experimental data on one hand and formulas Eqs.…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…Shear was studied by Deng et al (24), but was zero in the present study, hence a 3 and b 3 are irrelevant in the present experiment. When the strains E and E zz and stresses S , S zz were calculated from the experimental data on one hand and formulas Eqs.…”
Section: Methodsmentioning
confidence: 66%
“…After examining the application of the formula to experimental data on skin, Tong and Fung (28) concluded that the third order terms contribute little to the improvement of accuracy of the stress-strain law, and recommended dropping them in further mathematical modeling of soft tissue mechanics. The shear term has been shown to be correct in representing the results of torsion experiments of blood vessels by Deng et al (24), who used the results to evaluate the shear modulus, G, of the arterial wall. On specializing the formula in (28) to blood vessel and emphasizing the linear and nonlinear terms, we get Eq.…”
Section: Discussionmentioning
confidence: 99%
“…A common set of special problem features that leads to simplifying models includes "small" vessel wall thickness allowing a reduction from three-dimensional models to two-dimensional shell models, and cylindrical geometry of a section of an artery where no branching is present allowing the use of cylindrical shell models. Neglecting bending rigidity of arteries, studied in [18,21], reduces the shell model to a membrane model. Further simplifications include axial symmetry of the loading exerted by the blood flow to the vessel walls in the approximately straight cylindrical sections, leading to axially symmetric models with a potential of further reduction to one-dimensional models.…”
mentioning
confidence: 99%
“…In vivo tests on rabbit mesenteric arteries by Gorisch and Boergen (4) showed no contraction under 75°C, and Deng et al (1) found that temperatures between 25 and 37°C had a small effect on the shear modulus of rat aortas under multiaxial loading. Herrera et al (7) reported contradictory effects of temperature on isometric tests performed in the range of 5-37°C, where a rise of temperature induced contraction in rat aortas while relaxing pig renal arteries.…”
mentioning
confidence: 99%